Placebo Effects on the Immune Response in Humans: The Role of Learning and Expectation - Albring, Antje; Wendt, Laura; Benson, Sven; Witzke, Oliver; Kribben, Andreas; Engler, Harald; Schedlowski, Manfred (PLOS ONE, 2012)
Placebo responses are primarily mediated via two neuropsychological mechanisms: patients’ expectation towards the benefit of a treatment and associative learning processes. Immune functions, like other physiological responses, can be modulated through behavioral conditioning. However, it is unknown whether learned immune responses are affected by the number of re-expositions to the conditioned stimulus (CS) during evocation. Moreover, it is unclear whether immune functions can also be modulated through mere verbally induced expectation. In the experiments reported here, we investigated in healthy male volunteers with an established model of learned immunosuppression whether a single re-exposition to the CS is able to induce a behaviorally conditioned immunosuppression. This conditioned immunosuppression is reflected through a significantly decreased interleukin (IL)-2 production by anti-CD3 stimulated peripheral blood mononuclear cells. Our data revealed that in contrast to four CS re-expositions (control group n = 15; experimental group n = 17), a single CS re-exposition was not sufficient to significantly suppress IL-2 production (control group n = 9, experimental group n = 10). Furthermore, we could demonstrate that mere expectation of taking an immunosuppressant did not cause an immunosuppressive response (n = 8–9 per expectation condition). Together, these findings extend our knowledge about the kinetics and mechanisms of placebo-induced immunosuppression and provide therewith information for designing conditioning protocols, which might be employed as a supportive therapy in clinical settings.